2019
DOI: 10.1002/jbm4.10200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FES‐Rowing Exercise on the Time‐Dependent Changes in Bone Microarchitecture After Spinal Cord Injury: A Cross‐Sectional Investigation

Abstract: Disuse osteoporosis is a serious, secondary consequence of spinal cord injury (SCI). Numerous pharmacological and exercise therapies have been implemented to mitigate bone loss after SCI. However, these therapies have not been shown to improve bone density, potentially because of insufficient duration and magnitude of loading and/or inability of imaging modalities to capture changes in bone microarchitecture. In this cross-sectional study, we evaluated bone microstructure of the distal tibia and radius using H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Due to these inherent limitations, significant improvements in physiological markers of fitness such as bone density, which is load-dependent and may require longer exercise durations against higher resistances, have not been well reproduced with electrical stimulation systems [14][15][16][17]. Many of the significant physiological improvements that have been cited typically come only after extensive long-term training regimens, which may not be a feasible or appealing commitment to most people with paralysis.…”
mentioning
confidence: 99%
“…Due to these inherent limitations, significant improvements in physiological markers of fitness such as bone density, which is load-dependent and may require longer exercise durations against higher resistances, have not been well reproduced with electrical stimulation systems [14][15][16][17]. Many of the significant physiological improvements that have been cited typically come only after extensive long-term training regimens, which may not be a feasible or appealing commitment to most people with paralysis.…”
mentioning
confidence: 99%
“…This leads to a rapid and significant bone loss of 45% in the pelvis and 25% in the legs [46]. It has been previously shown that those with a longer PLOS ONE time since injury have relatively lower trabecular BMD and thickness and FESRT coupled with pharmacotherapy can counter the negative time-dependent effects of SCI on bone density and microstructure [31]. Our current results indicate that early application of sufficient load to sub-lesional bones via FESRT without pharmacotherapy can have a significant effect in preserving BMD, specifically in the involved pelvic region compared to SOC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in able-bodied individuals indicate that improved body composition [ 23 , 24 ] and cardiovascular fitness [ 25 , 26 ] directly relate to exercise intensity. In SCI, higher intensity exercise is more effective in increasing peak oxygen uptake [ 27 29 ] and may be associated with higher resultant lean mass and bone density [ 16 , 30 , 31 ]. Indeed, hybrid FES exercise at higher exercise intensities holds promise to mitigate adiposity, sarcopenia, and metabolic dysregulation [ 32 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, higher total work output was associated with greater BMD gain. For example, Lambach et al [ 106 ] reported that a higher magnitude of loading and more weekly training sessions were both associated with less trabecular vBMD loss at the proximal femur in persons that were undergoing FES rowing, and Draghici et al [ 142 ] reported that total distance rowed and peak foot reaction force were positively associated with the preservation of the distal tibia trabecular thickness in persons that were undergoing FES rowing, when these factors and SCI duration were incorporated into stepwise regression models. Similarly, Bloomfield et al [ 96 ] reported that distal femur aBMD was improved (+17.8% vs. the baseline) in a subgroup of persons who achieved power outputs >18 watts (W) during FES cycling, while aBMD was not improved in those with lower power output (<12 W, BMD change +0.2%) or in non-exercising controls (−2.3% vs. the baseline) and Frotzler et al [ 134 ] reported that FES cycling improved the total and trabecular vBMD at the distal femur with participants averaging ~18 W power output.…”
Section: Common Parameters To Improve Bmd After Scimentioning
confidence: 99%